2014
DOI: 10.1007/s12029-014-9607-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival from Anal Cancer Among Hispanics—Puerto Rico, 2000–2007

Abstract: Our findings establish baseline survival data for anal cancer in Hispanics from Puerto Rico. Since now, the national guidelines for anal cancer screening and treatment are on their way to be determined; baseline information about survival will allow monitoring the efficacy that standardized screening programs may eventually have in increasing anal cancer survival in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…For example, Puerto Rican young men showed a 20% higher incidence of anal cancer than US Hispanics, 6 and after only three years of a diagnosis, men in PR have lower relative survival estimates than white men in the US. 7 …”
Section: Introductionmentioning
confidence: 99%
“…For example, Puerto Rican young men showed a 20% higher incidence of anal cancer than US Hispanics, 6 and after only three years of a diagnosis, men in PR have lower relative survival estimates than white men in the US. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted has reported an increased risk of cervical cancer in this population (compared to mainland US), multiple barriers to cervical cancer screening [5,6], low awareness of HPV and the HPV vaccine [7], increasing trends of anal cancer [8,9] and a higher burden in the incidence and mortality from penile cancer in Puerto Rican men compared with other racial/ethnic groups in the US [10]. The significance of these studies led to multiple efforts from the academia, various local community coalitions, the medical community and other health professionals in PR, aiming to increase community engagement and capacity to reduce the burden of HPVassociated cancers in the island [3,6,[10][11][12][13][14][15][16][17]. All these accomplishments led to an increase in vaccine uptake over time, and thus higher HPV vaccination rates in PR compared to mainland US.…”
Section: Introductionmentioning
confidence: 99%
“…Major ndings included an increased risk of cervical cancer in this population compared to mainland US, multiple barriers to cervical cancer screening (5,6), low awareness of HPV and the HPV vaccine (7), increasing trends of anal cancer (8,9) and a higher burden in the incidence and mortality from penile cancer in Puerto Rican men compared with other racial/ethnic groups in the US (10). The magnitude of these needs led to multiple efforts from academia, various local community coalitions, the medical community and other health professionals in PR, aiming to increase community engagement and capacity to reduce the burden of HPV-associated cancers (6,(10)(11)(12)(13)(14)(15)(16)(17)(18). All these accomplishments led to increases in vaccine uptake over time, and thus higher HPV vaccination rates in PR compared to mainland US.…”
Section: Introductionmentioning
confidence: 99%